A Catastrophic Picture; Recurrent and Multiple Embolisms of Left Atrial Myxoma: Case Report - Colak, M. Cengiz; Kocaturk, Hasan; Bayram, Ednan (Ortadogu Ad Pres & Publ Co, 2011)
This report describes an unusual case of extensive multiple peripheral embolisms caused by a left atrial myxoma involving cerebral arteries, abdominal aorta and its branches in a 46-year-old patient. Embolism of left atrial myxoma is an uncommon but a well-known cause of peripheral and cerebral ischemia. Distal embolization is often the first presentation in most cases, with the central nervous system being the most common site. Distal embolization generally results from tumor fragmentation, or, less often, from complete tumor detachment, causing syncope, dyspnea, neurologic symptoms, or ischemic limb pain. Myxomas might give rise to embolism large enough to cause vascular occlusion, as in this case. This is the first case experienced initial peripheral embolism followed simultaneously by subsequent cerebral and abdominal/renal arterial embolisms originating from left atrial myxoma. Diagnosis was previously based on the transthroracic echocardiography and confirmed with histopathological evaluation of the resected material. We present a very interesting case of a myxoma leading to multiple embolisms concurrently with a catastrophic consequence despite aggressive attempts.
Katastrofık bir tablo: Sol atriyal miksoma kökenli multipl ve rekürren emboliler
Keywords: Heart atria; myxoma; embolism